Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f:\mathbb R \to \mathbb R$ be differentiable such that $f(x/2)=f(x)/2$ for any $x\in \mathbb R$. How can I prove that $f(x)=f'(0)x$, for any $x\in \mathbb R$? It seems easy, but I don't know why, I couldn't prove it.

I need help, thanks.

share|cite|improve this question

Since $f$ is differentiable at $0$, the limit

$$ \lim_{n\to\infty}\frac{f(2^{-n}x)-f(0)}{2^{-n}x} $$

must exist for all $x\ne0$ and be independent of $x$. The first term doesn't depend on $n$ due to the given functional equation, so we must have $f(0)=0$ and $f(2^{-n}x)/(2^{-n}x)=f'(0)$. The result follows by substituting $n=0$.

share|cite|improve this answer
Great solution! – Adar Hefer Feb 11 '13 at 21:06
Great. Note that $f(0)=f(0)/2$ so $f(0)=0$ from the equation. – 1015 Feb 11 '13 at 21:11

Essentially the same answer as joriki, with a slightlly different argument.

Note that $f(0)=f(0)/2$ by the functional equation so $f(0)=0$.

Now for all $x\neq 0$, an easy induction shows: $$ \frac{f(x)}{x}=\frac{f(x/2^n)}{x/2^n}=\frac{f(x/2^n)-f(0)}{x/2^n-0}. $$ Taking the limit as $n$ tends to $+\infty$, $$ \frac{f(x)}{x}=f'(0). $$

share|cite|improve this answer
up vote 1 down vote accepted

Using the Taylor formula with Lagrange reminder, there is a $c\in \mathbb R$ such that $f(x)=f(\frac {x}{2}+\frac {x}{2})=f(\frac {x}{2})+f'(c)\cdot\frac{x}{2}\implies f(x)=\frac {f(x)}{2}+f'(c)\cdot\frac{x}{2}\implies f(x)=f'(c)\cdot x$

Now we derive the last expression, we have $f'(x)=f'(c)$, for every $x\in \mathbb R$. then in particular $f'(0)=f'(c)$.

Then $f(x)=f'(0)\cdot x$

share|cite|improve this answer

Let $g(x)=f(x)/x$. Then $f$ differentiable implies that $g$ is continuous.

Then $f(x)=xg(x)$ and hence $g(x/2)=g(x)$ for all $x\in \mathbb R$.

It follows that $g(0)=\lim_n g(x/2^n)=g(x)$ for all $x \in \mathbb R$.

I think that this solution is one of the above ones disguised..

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.